A descriptive analysis of traumatic brain injury (TBI) cases seen at a tertiary hospital's trauma unit in South Africa over a one year period - Habtemariam, Dawit (Stellenbosch : Stellenbosch University, 2020)
Thesis (MMed)--Stellenbosch University, 2020.